Dynamic regime of the mesopause-lower thermosphere at midlatitudes of the northern hemisphere by radio meteor observations - Kashcheyev, B. L.; Oleynikov, A. N. (My University, 1994)
The coherent pulse Meteor Automatic Radar System (MARS) based at Kharkov (49 30 N, 36 51'E) was used to measure zonal winds in the altitude range 80-105 km In the period from November 1986 to December 1990. It was found that, for the greater part of the year, the zonal prevailing wind component was in the eastward direction. The change from eastward to westward direction begins in the lower thermosphere in February-March, propagating downwards to the mesosphere, and it remains there until June July. The structure of semidiurnal tides has general regularities at different sites. Annual variations in the monthly mean values of semidiurnal vertical wavelengths are practically the same, both in the northern and southern hemispheres. Wavelengths are more thsn 100 km m summer months, whereas they are less than 60 km in winter months. Studies of internal gravity wave (IGW) parameters m the height range of 80 105 km have shown that the internal gravity wave amplitude does not exceed 30 m/s, the vertical wavelength is in the range of [0-30 km, the horizontal wavelengths are 100-800 km and the horizontal phase velocities are in the range 20-160 m/s. The propagation and breaking of upward and downward IGW at heights of 80 100 km have been recorded.
Keywords: lower thermosphere; northern hemisphere; radio meteor observations